HUBUNGAN ANTARA TINGKAT STRES DENGAN KUALITAS HIDUP PASIEN HIPERTENSI USIA DEWASA AKHIR DI WILAYAH KERJA PUSKESMAS KARANGMALANG - Herlinda, Bella; Nabilah Nasywa Eka Pratiwi; Afida Nur Aulia; Khansa’ Faadhilah Hibatullah; Zahro Adzakia Qurrota A’yun; Leni Erlinda; Satriya Pranata (CV. Denasya Smart Publisher, 2025)
Hypertension is a prevalent non-communicable disease in late adulthood that may impair quality of life due to prolonged psychological stress. This study aimed to examine the correlation between stress levels and quality of life among hypertensive patients in late adulthood at the Karangmalang Public Health Center. A quantitative observational study with a cross-sectional design was conducted among 20 hypertensive patients aged 36-45 years, selected through purposive sampling. Stress levels were. Stress levels were measured using the Perceived Stress Scale (PSS-10), and quality of life was assessed using the WHOQOL-BREF instrument. Data were analyzed using univariate and bivariate methods with the Pearson correlation test. The result showed that most respondents experienced moderate stress (mean score = 16.4) and had a good quality of life (mean score = 95.25). Pearson’s analysis revealed a significant positive correlation between stress levels and quality of life (r = 0.624; p = 0.003). Moderate stress (eustress) was found to facilitate adaptive coping, enabling patients to maintain favorable well-being despite chronic illness. There is a asignificant relationship between stress level and quality of life in hypertensive adults. Moderate stress may serve an adaptive role, emphasizing the need for nursing interventions that integrate stress management and psychosocial support to enhance overall quality of life among hypertensive patients. The results of this study provide practical benefits for various parties. For the Puskesmas, they serve as a basis for strengthening promotive and preventive programs. For nurses, the findings can be used as a reference in providing holistic nursing care. For patients and the community, the study enhances understanding of the importance of stress management and social support in maintaining quality of life. Moreover, for researchers and educational institutions, these results can serve as a reference for further studies in community nursing.